Towards a Theory on Dominant Business Model Emergence of Marketplace Lending in Germany - Sabine Pur; Stefan Huesig; Christoph Schmidhammer (Credit and Capital Markets – Kredit und Kapital, 2023)
In this paper, we analyze the business models of Germany's biggest lending platforms smava, auxmoney, and Lendico to identify a standard business model as a dominant design in this industry. We use a mixed method approach in which a case study at firm level is conducted to analyze and contrast the business models together with their business model components. This qualitative analysis is complemented with a quantitative test of their total asset annual growth rates to triangulate the qualitative analysis. The results indicate that all three companies started with a similar approach but evolved over time into entirely different business model variants. This seems to contradict the previous theory of the emergence of standard business models and dominant designs. At first glance, an increasing convergence of business models over time into a standard business model in the German lending platform industry was not consistent with our results. However, we suggest to explain this contradiction by taking a closer look at the global context of the industry. The origin of lending platforms was pioneered outside the German market by firms such as Zopa (UK) or later Prosper and Lending Club (USA). We hypothesize based on initial evidence that the German lending platforms have largely adopted the business models of the early movers and later modified them according to their local value network such as local market, regulation, and competition conditions. Thereby we propose that the deficient standard business model as a dominant design or a winner takes all market outcome in the lending platform industry might depend on localized demand and regulative heterogeneity.
Keywords: G23; G51; L11; L84; M13; O16; O33; P45; 330; inTech; Lending Platform; Dominant Design; Business Model; StandardBusiness Model; Two-Sided Markets